Temperature and stoichiometry effect on microstructural and ferroelectric properties of Pb(Zr1-xTix)O3 thin films prepared by chemical soulution deposition - Foschini, C. R.; Li, J. F.; Suchicital, C. T A; Viehland, D.; Stojanovic, B. D. [UNESP]; Varela, José Arana [UNESP] (My University, 2004)
Lead zirconate titanate (PZT) solutions were prepared using a polymeric precursor method, Zr n-propoxide and Ti i-propoxide were used as starting materials with ethylene glycol and water as solvents. The PZT solution was spin-coated on Pt/Ti/SiO2/Si substrates, baked on a hot plate, and finally heat-treated in a tube furnace between 400 and 800°C. The surface morphology and grain size of the films were characterized by atomic force microscopy (AFM), using a tapping mode with amplitude modulation. The films, thermal annealed at temperatures higher than 500°C, exhibited a dense microstructure, without noticeable cracks or voids. Electrical properties were investigated as a function of composition and annealing temperature.
Keywords: Amplitude modulation; Annealing; Atomic force microscopy; Characterization; Composition; Ferroelectricity; Lead compounds; Microstructure; Organic solvents; Polyethylene glycols; Silica; Stoichiometry; Annealing temperatures; Dense microstructures; Electromechanical response; Thin films